Assessment of Climate Change in the Southwest United States A Report Prepared for the National Climate Assessment - Garfin, Gregg; Jardine, Angela; Merideth, Robert; Black, Mary.; LeRoy, Sarah; SpringerLink (Online service) (Washington, DC : Island Press/Center for Resource Economics : Imprint: Island Press, 2013)
Prepared for the 2013 National Climate Assessment and a landmark study in terms of its breadth and depth of coverage, this report blends the contributions of 120 experts in climate science, economics, ecology, engineering, geography, hydrology, planning, resources management, and other disciplines to provide the most comprehensive, and understandable, analysis to date about climate and its effects on the people and landscapes of Arizona, California, Colorado, Nevada, New Mexico, and Utah$1 (Bincluding the U.S.-Mexico border region and the lands of Native Nations. What is the climate of the Southwest like today? What has it been like in the past, and how is it projected to change over the 21st century? How will that affect water resources, ecosystems, agricultural production, energy supply and delivery, transportation, human health, and a host of other areas? How vulnerable is the region to climate change? What else do we need to know about it, and how can we limit its adverse effects? In addressing these and other questions, the book offers decision makers and stakeholders a substantial basis from which to make informed choices that will affect the well-being of the region$1 (Bs inhabitants in the decades to come.s
Acknowledgements -- Abbreviations and Acronyms -- 1. Summary for Decision Makers -- Part 1. Context. 2. Overview -- 3. The Changing Southwest -- Part 2. Weather and Climate of the Southwest. 4. Present Weather and Climate: Average Conditions -- 5. Present Weather and Climate: Evolving Conditions -- 6. Future Climate: Projected Average -- 7. Future Climate: Projected Extremes -- Part 3. Effects of Climate Change in the Southwest. 8. Natural Ecosystems -- 9. Coastal Issues -- 10. Water: Impacts, Risks, and Adaptation -- 11. Agriculture and Ranching -- 12. Energy: Supply, Demand, and Impacts -- 13. Urban Areas -- 14. Transportation -- 15. Human Health -- 16. Climate Change and U.S.-Mexico Border Communities -- 17. Unique Challenges Facing Southwestern Tribes -- Part 4. Options and Research Needs. 18. Climate Choices for a Sustainable Southwest -- 19. Moving Forward with Imperfect Information -- 20. Research Strategies for Addressing Uncertainties -- References -- Glossary -- Author and Review Editors -- Reviewers.
Keywords: Environmental sciences; Geology; Agriculture; Climatic changes; Environment; Climate Change; Atmospheric Sciences; Coastal Sciences; Agriculture; Water Policy/Water Governance/Water Management